Monoaminergic and Histaminergic Strategies and Treatments in Brain Diseases - Di Giovanni, Giuseppe; Svob Strac, Dubravka; Sole, Montse; Unzeta, Mercedes; Tipton, Keith F.; Mück-Šeler, Dorotea; Bolea, Irene; Della Corte, Laura; Nikolac Perkovic, Matea; Pivac, Nela; Smolders, Ilse J.; Stasiak, Anna; et al. (Frontiers in Neuroscience, 2016)
The monoaminergic systems are the target of several drugs for the treatment of mood, motor and cognitive disorders as well as neurological conditions. In most cases, advances have occurred through serendipity, except for Parkinson’s disease where the pathophysiology led almost immediately to the introduction of dopamine restoring agents. Extensive neuropharmacological studies first showed that the primary target of antipsychotics, antidepressants, and anxiolytic drugs were specific components of the monoaminergic systems. Later, some dramatic side effects associated with older medicines were shown to disappear with new chemical compounds targeting the origin of the therapeutic benefit more specifically. The increased knowledge regarding the function and interaction of the monoaminergic systems in the brain resulting from in vivo neurochemical and neurophysiological studies indicated new monoaminergic targets that could achieve the efficacy of the older medicines with fewer side-effects. Yet, this accumulated knowledge regarding monoamines did not produce valuable treatments for diseases where no monoaminergic drug has been shown to be effective. Here, we emphasize the new therapeutic and monoaminergic-based strategies for the treatment of psychiatric diseases. We will consider three main groups of diseases, based on the evidence of monoamines involvement (schizophrenia, depression, obesity), the identification of monoamines in the diseases processes (Parkinson’s disease, addiction) and the prospect of the involvement of monoaminergic mechanisms (epilepsy, Alzheimer’s disease, stroke). In most cases, the clinically available monoaminergic drugs induce widespread modifications of amine tone or excitability through neurobiological networks and exemplify the overlap between therapeutic approaches to psychiatric and neurological conditions. More recent developments that have resulted in improved drug specificity and responses will be discussed in this review.